Promosi Kesehatan Tentang Covid-19, Pencegahan Dan Penanganan Hipertensi Pada Lansia - Bahtiar, Heri; Ariyanti, Maelina; Supriyadi, Supriyadi (Jurnal LENTERA, 2021)
Human Development Index has three elements, they are health, education attained and standard of living or often called the economy. Knowledge regarding the prevention and handling of COVID-19 and Hypertension in Elderly needs to be disseminated to reduce the number of COVID-19 cases considering the spread of this virus between humans and humans. The incidence of hypertension was also quite a lot and major cause of degenerative disease. The incidence of COVID-19 in West Nusa Tenggara (NTB) Province has also experienced a significant increase since the announcement of the first positive cases on March 24, 2020. On April 21, 2020, there were 108 cases, with 11 recovered and 4 people. die. The number of COVID-19 sufferers in Mataram was 43 cases, while hypertension cases in Mataram, especially in Pondok Perasi, were 41 people. Health education need to be attention for society regarding the prevention and control the spread of COVID-19 and Hypertension increases knowledge and urges the public to suppress the chain of spread of the Corona Virus which can cause COVID-19 and prevent recurrence of hypertension in the elderly. The target of this public service was the Community in the Bintaro Ampenan, Mataram, the aim of this public service was to providing the understanding of community about counseling on the prevention of covid-19, washing hands properly, and providing materials for the prevention of covid-19 transmission by distributing free masks and counseling on hypertension. These activities have been carried out well. The response from residents was very good and they hoped that similar activities were carried out regularly